Computer assisted learning versus conventional teaching: a questionnaire based study - Jain, Shipra; Sharma, Kopal; Jain, Pushpawati; Singh, Sakshi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Animal experiments have ethical concerns thus practical sessions mean demonstration classes. Incorporation of novel teaching methods in pharmacology is the need of the hour when there is extensive use of computers among students. The present study was conducted to analyse and compare the knowledge gained by students through traditional demonstration lectures versus Computer assisted learning (CAL) sessions. Methods: This study was done on 112 second professional MBBS students after taking informed consent. They were divided in 2 groups viz. CAL group and Traditional teaching group and were taught experimental pharmacology topics using different teaching methods. The performance of the students in the two groups was then compared based on questionnaire. Student’s perception on use of CAL was also assessed. Results: A statistically significant difference in performance was seen among the students in the traditional teaching group and CAL group. In CAL group, the average scores for the Rabbit’s eye, Dog’s blood pressure, Animals used in Experimental Pharmacology and Screening methods sessions were 9.07, 8.3 and 3.8 respectively while in traditional teaching group the scores were 8.4, 7.8 and 3.4 respectively. Similarly, in frog’s heart session, CAL group scored higher (7.14) than traditional group (6.79). 76.8% students strongly agreed that CAL sessions were useful and 100% students strongly agreed that traditional lectures are difficult to retain. Conclusions: The study concludes that CAL is a promising teaching option when compared to traditional demonstration lectures for undergraduate practical pharmacology classes.